The Symbolic Violence in Madrasah - Muri'ah, Siti; Gianto, Gianto (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
Violence is identical with power. Violence is a practice result of power. When a class dominates another class, the process will produce violence. The mechanism of violence carried out by the dominant class against the dominated class slowly and smoothly. Education, according to Bourdieu, is only a tool to maintain the existence of the dominant class. The dominant class forces the dominated class to behave and follow the culture of the dominant class throughout the school. Schools influence students' attitudes and habits with dominant classroom culture. This research is a qualitative descriptive. This research was conducted at Madrasah Ibtidaiyah Negeri (MIN) Balikpapan and in Madrasah Ibtidaiyah Negeri (MAN) 2 Nganjuk. Resources in this study are the headmaster of Madrasah, deputy, teachers, subject teachers, boarding teachers and students. Data collection techniques used in this study is observation, interviews and documentation. Data analysis used is content analysis. From the study, it can be concluded that symbolic violence in Madrasah Ibtida'iyah Negeri (MIN) Balikpapan and Madrasah Ibtida'iyah Negeri (MIN) 2 Nganjuk are manifested in almost all madrasah activities. The symbolic form of violence that researchers found was that students were forced to practice upper-class habit published in wall magazine, students were forced to accept high-class habit in the form of pictures or persuasive sentences (seducing) subtly. For example, 6 S mottos: Smile, Greet, Greetings, Shaking hand, Polite, and Saying Salaam Before entering class.